Zasady intelektualizmu - Drozdowicz, Zbigniew (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2011)
In the view, which is proposed here, intellectualism is what brings together and not what divides, and its rules are placed in some manner over every distinction. This means, that intellectualism is being treated by me as a collective work. Its most early versions occurred along the occurrence of first philosophers. Later on, they were often corrected, perfected or also so immensely changed, that under more than one condition they varied from the originals. Many philosophers took part in the making of this work, but some had a lesser and some greater influence. To those, who significantly contributed to its emergence and functioning in European philosophy and science, there belonged such authors like Socrates, Descartes, and Popper.